Effect of functionalization of multi-walled carbon nanotube on mechanical and viscoelastic properties of polysulfide-modified epoxy nanocomposites. (March 2017) - Wu, Yeping; Gu, Zhongyun; Chen, Maobin; Zhu, Chunhua; Liao, Hong
In order to obtain epoxy compounds with excellent mechanical properties without compromising other desired properties, pristine- or carboxyl-functionalized multi-walled carbon nanotube (p-MWCNT or f-MWCNT) along with polysulfide were incorporated into an amine-cured epoxy resin. Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy analyses proved the existence of carboxyl groups on the surface of f-MWCNT. Adding 0.1 wt% f-MWCNT significantly improved the tensile strength and impact strength of the epoxy nanocomposites by 104% and 47%, respectively. However, adding p-MWCNT had little effect on the mechanical properties of the nanocomposites. The glass transition temperature of the f-MWCNT/epoxy nanocomposites were also much higher than neat epoxy matrix and p-MWCNT/epoxy nanocomposites. The fracture surface morphology and dynamic mechanical analysis results indicated that the interfacial interactions between f-MWCNT and the epoxy matrix were much stronger than that of p-MWCNT, which ensured the much-improved mechanical properties.